SUSTAINABLE TERRITORIAL PLANNING INVOLVING THE PARTICIPATION OF INHABITANTS IN ECUADOR AND QUITO - Margherita Ciervo (Bollettino della Società Geografica Italiana)
This paper presents a research in the field focused on participation planning policies realized in Ecuador and specifically in the Metropolitan District of Quito. The aim is to evaluate and verify whether the realized planning has involved the participation of and has been developed with inhabitants, or if it is more or less a persuasive representation. The attention is on the process and power relations to recognize and explicate the subtended political choices, especially to correlate problems to key elements of sustainable territorial planning (inequality, ecological disequilibrium, social tensions and conflicts). The case study shows that participation planning is basically produced and legitimated by institutional-politic initiatives, both at the national and urban scales, with contradictions between symbolic and material fields, and between form and substance. Finally, we think that participation planning assumes some characteristics of a propagandistic initiative and seems functional in regard to the consolidation of existent power’s relations (historically determined by colonization, capitalism and neoliberalism).